Neuro-Epigenetic Indications of Acute Stress Response in Humans: The Case of MicroRNA-29c - Vaisvaser, Sharon (Public Library of Science, 2016)
Stress research has progressively become more integrative in nature, seeking to unfold crucial relations between the different phenotypic levels of stress manifestations. This study sought to unravel stress-induced variations in expression of human microRNAs sampled in peripheral blood mononuclear cells and further assess their relationship with neuronal and psychological indices.